Effect of High Volume Fly Ash on Shrinkage of Self-compacting Concrete. (2015) - Kristiawan, Stefanus A.; Aditya, M. Taib M.
Abstract: Self-compacting concrete (SCC) has been produced incorporating fly ash as cement replacement at 35%, 55% and 65% by weight. The flowability, fillingability and passingability of these concrete were assessed by combination of the following test methods: flow table, J-Ring, L-Box, Box Type and V-funnel test. For each mix proportion of SCC, six cylinder specimens (75 mm x 275 mm) were cast for shrinkage measurements following the RILEM Recomendation. Three of them were used for measurement of drying shrinkage while the other three were used for autogenous shrinkage. The results show that a higher cement replacement by fly ash tends to decrease both drying and autogenous shrinkage. Estimations of shrinkage using ACI 209R, CEB-FIP 1990 and Ross's method suggest that ACI 209R and CEB-FIP 1990 provide accurate prediction than Ross's model.